A novel function of vitellogenin subdomain, vWF type D, as a toxin-binding protein in the pufferfish Takifugu pardalis ovary. (15th September 2017) - Yin, Xianzhe; Kiriake, Aya; Ohta, Akira; Kitani, Yoichiro; Ishizaki, Shoichiro; Nagashima, Yuji
Abstract: Marine pufferfish of the Tetraodontidae family contain high levels of tetrodotoxin (TTX) in the liver and ovary. TTX is suggested to transfer from the liver to the ovary in female pufferfish during maturation. TTX in pufferfish eggs may act as a repellent against predators and as a sexual pheromone to attract male pufferfish. The toxification mechanism of the pufferfish ovary is poorly understood. Here we evaluated the chemical form of TTX and its related substances in the ovary of the panther pufferfish Takifugu pardalis by LC-ESI/MS. TTX and its analogs 4- epi -TTX, 4, 9-anhydroTTX, deoxyTTX, dideoxyTTX, and trideoxyTTX were detected in a low molecular weight fraction by Sephacryl S-400 column chromatography. The finding of an unknown TTX-related substance in a high molecular weight fraction from the Sephacryl S-400 column suggested the occurrence of toxin-binding protein in the ovary. The toxin-binding protein in the ovary was purified by ion-exchange HPLC, gel filtration HPLC, and SDS-PAGE. Amino acid sequencing and cDNA cloning revealed that the toxin-binding protein, TPOBP-10 ( Takifugu pardalis ovary toxin-binding protein with a molecular mass of 10 kDa) was homologous with the predicted vitellogenin-1-like protein [ Takifugu rubripes ] subdomain, a von Willebrand factor type D domain. TPOBP-10 mRNA was highly expressed in the ovary and liver and less in other organs of female individuals based on RT-PCR. These findings reveal a novel function of the vitellogenin subdomain as binding with TTX-related substances, and its involvement in the toxification of the pufferfish ovary. Highlights: Tetrodotoxin (TTX) is suggested to transfer from the liver to the ovary in female pufferfish during maturation. An unknown TTX-related substance was found in a high molecular weight fraction in the pufferfish Takifugu pardalis ovary. This indicates the occurrence of toxin-binding protein in the ovary. The toxin-binding protein was isolated and identified as a vitellogenin subdomain, a von Willebrand factor type D domain. This study reveals a novel function of the vitellogenin subdomain as binding with pufferfish toxin.